Prostorska porazdelitev faktorja ugodja na temelju numeričnega modeliranja naravne konvekcije - Glavnik, Aleš (Strojniški vestnik, 2002)
This paper discusses the problem of providing a comfortable indoor environment with heating and air-conditioning systems. With the use of an algorithm the thermal sensation and the degree of discomfort of people can be presented and acceptable thermal environmental conditions for comfort can be specified. The presented method for designing the thermal comfort is important for engineering practise and shows how to provide a comfortable indoor environment with a low health risk for the occupants.
Keywords: klimatizacija; prenos toplote; prenos snovi; konvekcija naravna; dinamika tekočin; ogrevanje; toplotno ugodje